Creating the nursing care map in the evaluation of kidney transplant candidates: A scoping review and narrative synthesis - Guillermo Pedreira‐Robles; Paloma Garcimartín; Anna Bach‐Pascual; Dolors Giró‐Formatger; Dolores Redondo‐Pachón; Victoria Morín‐Fraile (Wiley, 2023)
Abstract Aims To analyse the aspects involved in the care of individuals assessed as kidney transplant candidates and to identify the role of nurses in providing specialised care for this population. Design Scoping review. The results were summarised using a narrative synthesis technique. Data Sources A review of the literature published between 2001 and 2021 was conducted between October and November 2021 using PubMed, CINAHL and SciELO. Review Methods The research team agreed on a search strategy based on clinical practice guidelines for assessing kidney transplantation candidates. Quantitative, qualitative and mixed methods studies published in peer‐reviewed journals in English, Spanish, French and Portuguese were included. Results A total of 377 studies were identified, and 49 articles were included after the inclusion and exclusion criteria were applied. The narrative synthesis was structured into four themes: Physical needs; Psychological and quality of life needs; Education and adherence needs; and Nurses' role. Conclusion Nursing assessment of kidney transplantation candidates should encompass physical, psychosocial and adherence aspects. A variety of methodologies and resources are available for this assessment. Nurses contribute to coordinating access to kidney transplantation, aiming to improve adherence to an appropriate lifestyle to prevent patients from being excluded from kidney transplantation or suffering from kidney transplantation-related complications. Impact Based on our findings, we managed to design a nursing care map for kidney transplantation candidates combining the main elements of nursing care that should be incorporated into this process. Advanced practice nursing professionals play a crucial role in accessing renal transplant care.